“Ruma Besi” Site as a Media Learning History at Madrasah Aliyah Sairun, Rhun Islands-Banda Naira - Namen, Nursyifa (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
The purpose of this study is to show how the historical site